2020
DOI: 10.1108/reps-11-2019-0145
|View full text |Cite
|
Sign up to set email alerts
|

Digital transformation, development and productivity in developing countries: is artificial intelligence a curse or a blessing?

Abstract: Purpose The entire world is now witnessing the Fourth Industrial Revolution and Artificial Intelligence (AI) is indeed altering the lives of the many in both developing and developed countries. Massive digital transformations are affecting the economies of those countries and are bringing with them many promised merits, as well as many challenges to face. This paper aims to examine the relationship between digital transformation (as a one facet of the fourth revolution and AI trends) on one side, and economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 10 publications
(10 reference statements)
1
57
1
8
Order By: Relevance
“…However, the impact of digital transformations [17] is ambiguous not only on the economies of different countries [18,19], but also on the labor market and productivity. On the one hand, they contribute to the creation of a new workforce (virtual, not real, with higher productivity and efficiency) [20], and on the other, they affect the composition of existing (created and lost) jobs [21] and labor productivity [22].…”
Section: Methodsmentioning
confidence: 99%
“…However, the impact of digital transformations [17] is ambiguous not only on the economies of different countries [18,19], but also on the labor market and productivity. On the one hand, they contribute to the creation of a new workforce (virtual, not real, with higher productivity and efficiency) [20], and on the other, they affect the composition of existing (created and lost) jobs [21] and labor productivity [22].…”
Section: Methodsmentioning
confidence: 99%
“…New technology such as the human-machine interface helps in extracting knowledge owned by workers and also enhances workers' efficiency by freeing time from repetitive tasks for more complex work [45]. Aly [46] examined the relationship between digital transformation and labor productivity and employment in developing countries. The research found a positive relationship between digital transformation and labor productivity.…”
Section: Technology Acceptance Modelmentioning
confidence: 99%
“…A negative relationship was reported between competitive pressure and continuous digital disruption (Bughin and Zeebroeck, 2017). Previous findings also showed a positive insignificant impact between User expectation and continuous digital disruption (Orsatti and Riemer, 2015;Tornjanski et al, 2017, Aly, 2020. The research findings of (Hoong et al, 2017;Elkaseh et al, 2016) indicated an insignificant impact between advancement of technology and continuous digital disruption.…”
Section: Discussion On Findingsmentioning
confidence: 66%